Peran Moderasi Komisaris Independen Terhadap Firm Attributes dan Penghindaran Pajak: Studi Empiris Perbankan di Indonesia - Anggraeni, Silvia Arvina; Mardi; Dwi Kismayanti Respati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze how leverage and capital intensity ratios affect tax avoidance practices, with independent commissioners acting as a moderating factor. This research applies a quantitative approach to secondary data with documentation techniques and literature review. The population in the study consisted of banking sub-industry companies available on the Indonesia Stock Exchange since 2020-2022. The sample calculation applies purposive sampling technique with a total sample of 84 companies. The analysis method applied in the study is through panel data regression analysis techniques from moderated regression analysis analyzed on E-Views 12 student lite software. The results obtained from this study have shown that leverage and capital intensity ratio have a positive and significant effect on tax avoidance. Furthermore, independent commissioners weaken the influence of leverage on tax avoidance, while not being able to moderate the capital intensity ratio for tax avoidance of industrial companies in the banking sub-sector on the Indonesia Stock Exchange.